Topological phases of quasi-one-dimensional fermionic atoms with a synthetic gauge field - Takeshi Mizushima; Masatoshi Sato (New Journal of Physics, 2013)
We theoretically investigate the effect of intertube tunneling in topological superfluid phases of a quasi-one-dimensional Fermi gas with a Rashba-type spin–orbit interaction. It is shown that the effective Hamiltonian is analogous to that of a nanowire topological superconductor with multibands. Using a hidden mirror symmetry in the system, we introduce a new topological number that ensures the existence of non-Abelian Majorana zero modes even in the presence of intertube tunneling. It is demonstrated from the full numerical calculation of self-consistent equations that some of the Majorana modes survive against the intertube tunneling, when the number of one-dimensional tubes is odd in the y -direction. We also discuss a generalization of our consideration to nanowire topological superconductors.